Endosomes - Dikic, Ivan (Molecular Biology Intelligence Unit, 2006)
Endosomes are a heterogeneous population of endocytic vesicles and tubules that have captivated the interest of biologists for many years, partly due to their important cellular functions and partly due to their intriguing nature and dynamics. Endosomes represent a fascinating interconnected network of thousands of vesicles that transport various cargoes, mainly proteins and lipids, to distant cellular destinations. How endosomes function, what co-ordinates the molecular determinants at each step of their dynamic life cycle and what their biological and medical relevance is, are among the questions addressed in this book.